MPK1-426 Sykes Picot Agreement Map signed 8 May 1916 - Royal Geographical... (Wikimedia Commons, 2011)
Notice visuelle issue de Wikimedia Commons pour la demo du fonds documentaire.
Licence Public domain via Wikimedia Commons
Keywords: carte; plan; geographie; territoire; wikimedia commons